‘Author/Reader’ Dichotomy: Linguistic and Cognitive Intentions - Kononenko, Vitalii (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
The purpose of this research is to address the issue of the interaction between the author of a literary text and the reader in the system of linguocognitive intention. The article covers the problems of contextual interpretation of the author’s linguistic and artistic strategies, their personality traits, verbal means of creating the image of the author in the addressee’s consciousness. In order to get the image of the recipient of the text, one has to make subconscious inferences from the author’s comments, statements addressed to the reader, lyrical and epic digressions, etc. The analysis of the texts by modern Ukrainian authors – their linguopoetic paradigm and the intimization of speech technique deployed in order to produce a greater illocutionary effect on the addressee – has made it possible to establish the means and strategies which stimulate communicative process and enhance understanding between the author and the reader. Another problem highlighted in the research is critical perception of the text creator’s ego conception and the probability of providing feedback within the ‘author/reader’ dimension